Giant ovarian yolk sac tumor during late pregnancy: a case report and literature review - Wang, Qin; Zuo, Jianxin; Liu, Chong; Zhou, Huansheng; Wang, Wenjie (Frontiers in Oncology, 2024)
The manifestation of a giant ovarian yolk sac tumor during late pregnancy is relatively rare. A yolk sac tumor is a highly malignant germ cell tumor that originates from primitive germ cells. It is characterized by yolk sac differentiation in vitro. The frequency of prenatal examinations should be appropriately increased for ovarian tumors discovered during pregnancy. Furthermore, regular follow-up ultrasound should be performed, and tumor markers should be dynamically detected. If needed, imaging examinations such as computed tomography and magnetic resonance imaging should be combined to comprehensively investigate disease progression. If the tumor diameter and tumor marker levels rapidly increase during pregnancy, the possibility of malignancy increases. Therefore, exploratory laparotomy should be immediately performed to further improve subsequent treatment modalities, early diagnosis, early treatment, and prognosis. Herein, we report the case of a 28-year-old pregnant woman whose pregnancy was terminated at 29 weeks and 5 days. She complained of lower abdominal pain for 2 days. A pelvic mass was detected for 1 week, accompanied by increased levels of tumor markers such as serum alpha-fetoprotein, cancer antigen 125, carbohydrate antigen 724, and human epididymis protein 4. Imaging revealed the presence of a pelvic mass. At 32 weeks and 3 days of pregnancy, a cesarean section was performed, with a transverse incision in the lower uterine segment. Furthermore, pelvic adhesiolysis, omentectomy, right adnexectomy, right pelvic lymph node dissection, and pelvic metastasis peritonectomy were performed. The postoperative pathological diagnosis was yolk sac tumors of the ovary (stage IIB). Postoperatively, a five-cycle chemotherapy regimen comprising bleomycin, etoposide, and cisplatin was administered. During postoperative follow-up, the patient’s general condition was noted to be good, with the newborn and pregnant women ultimately achieving good outcomes. We reviewed the relevant literature to increase clinical doctors’ understanding of ovarian malignancy during pregnancy, guide treatment selection, and facilitate early intervention for associated diseases.